Hooking She3p onto She2p for myosin-mediated cytoplasmic mRNA transport - Singh, Nimisha (Proc Natl Acad Sci U S A, 2015)
The segregation of approximately two dozen distinct mRNAs from yeast mother to daughter cell cytoplasm is a classical paradigm for eukaryotic mRNA transport. The information for transport resides in an mRNA element 40–100 nt in length, known as “zipcode.” Targeted transport requires properly positioned actin filaments and cooperative loading of mRNA cargo to myosin. Cargo loading to myosin uses myosin 4 protein (Myo4p), swi5p-dependent HO expression 2 protein (She2p) and 3 protein (She3p), and zipcode. We previously determined a crystal structure of Myo4p and She3p, their 1:2 stoichiometry and interactome; we furthermore showed that the motor complex assembly requires two Myo4p⋅She3p heterotrimers, one She2p tetramer, and at least a single zipcode to yield a stable complex of [Myo4p⋅She3p⋅She2p⋅zipcode] in 2:4:4:1 stoichiometry in vitro. Here, we report a structure at 2.8-Å resolution of a cocrystal of a She2p tetramer bound to a segment of She3p. In this crystal structure, the She3p segment forms a striking hook that binds to a shallow hydrophobic pocket on the surface of each She2p subunit of the tetramer. Both She3p hook and cognate She2p binding pocket are composed of highly conserved residues. We also discovered a highly conserved region of She3p upstream of its hook region. Because this region consists of basic and aromatic residues, it likely represents part of She3p’s binding activity for zipcode. Because She2p also exhibits zipcode-binding activity, we suggest that “hooking” She3p onto She2p aligns each of their zipcode-binding activities into a high-affinity site, thereby linking motor assembly to zipcode.